(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2025)
In the article we will try to give brief information on how to improve a person’s memory and how to develop it. In order to become a perfect person, a person needs religious and world knowledge, and in order to receive so much knowledge, one must have a good memory.